Adoption of pig Artificial Insemination by pig keepers in Uganda through SAPLING supported artificial insemination service providers - Businge, Martha; Kugonza, Donald; Kasoro, Isaac; Ouma, Emily A.; Marshall, Karen (International Livestock Research Institute, 2024)
Reproductive aid techniques, such as artificial insemination (AI), have proven to be extremely effective in improving breed quality, resulting in increased output and productivity. Implementing AI reproductive techniques improves production conditions, lowers costs, and increases efficiency. The CGIAR initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) under the innovation package 1 sought to improve access to farmer preferred pig breeds through artificial insemination. The intended outcome being a strengthened pig genetic resource value chain through business models for AI service providers and potentially semen suppliers + capacity building of actors.